2005
DOI: 10.1039/b506688c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of lanthanoid ions on calcite

Abstract: The adsorption of 14 trivalent lanthanoid ions and yttrium ion (denoted by Ln3+) on calcite surfaces was investigated under various solution conditions of pH (pH = 6.8-7.8) and calcium ion concentration (pCa = -log[Ca2+]= 2.0 and 3.0), and different surface conditions of calcite crystals (well-developed and rough surfaces). The lanthanoid ions were equilibrated in a solution of ionic strength 0.1 mol dm-3(NaCl) saturated with calcite at 25.0 degrees C using excess (solid) calcite crystals suspended in solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Their diameter, 7.4 Å, is sufficient for easy diffusion of hydrated tripositive lanthanide ions and nitrate ions to the internal structure of the adsorbent. If we take into account that the radii of the tripositive lanthanides are in the range 1-1.25 Å [12], whereas the diameter of the water molecule and the ionic radius of the NO − 3 ion are 2.82 [40] and 1.79 Å [41], respectively, then we can see that the outer sphere nitrato lanthanide complex Ln(H 2 O) x NO 2+ 3 can accommodate to the zeolite Y pore structure. …”
Section: Tetrad Effect In the Lanthanides Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their diameter, 7.4 Å, is sufficient for easy diffusion of hydrated tripositive lanthanide ions and nitrate ions to the internal structure of the adsorbent. If we take into account that the radii of the tripositive lanthanides are in the range 1-1.25 Å [12], whereas the diameter of the water molecule and the ionic radius of the NO − 3 ion are 2.82 [40] and 1.79 Å [41], respectively, then we can see that the outer sphere nitrato lanthanide complex Ln(H 2 O) x NO 2+ 3 can accommodate to the zeolite Y pore structure. …”
Section: Tetrad Effect In the Lanthanides Adsorptionmentioning
confidence: 99%
“…Four parts were distinguished within the series: 57-60, 60-64, 64-68, and 68-71. Sawada et al [12] observed the tetrad effect in the distribution constants of the lanthanides on calcite.…”
Section: Introductionmentioning
confidence: 98%
“…The reason for the shrinking phenomenon of the unit cell volume is due to the smaller ionic radius of Tb 3+ (0.923 Å) as compared to that of La 3+ ion (1.032 Å). 39 The above observation further conrms the successful substitution of Tb 3+ ions in the crystalline LaF 3 lattices. All the above analysis indicates that Tb 3+ ions have been successfully doped into the lattice of LaF 3 nanomaterials.…”
Section: Xrd Studymentioning
confidence: 68%
“…Although the Er:Yb:SYB crystal, which combines the advantages of the YAB and YCOB crystals, can be grown by the Czochralski method and has large absorption cross-section and broad absorption band around 976 nm, the segregation coefficient of Yb 3+ ions is only 0.75 in this crystal [7]. The segregation coefficient less than 1 may be originated from the difference of ionic radii between Y 3+ (0.900 Å) and Yb 3+ (0.868 Å) ions [8] and the high Yb 3+ doping concentration in the crystal. Thus, lattice distortion and defects may exist in the Er:Yb:SYB crystal after the introduction of high Yb 3+ doping and then affect the performance of the 1.5-1.6 μm laser.…”
Section: Introductionmentioning
confidence: 99%
“…This is because that the radius of Lu 3+ ions (0.861 Å) is much closer to that of Yb 3+ ions (0.868 Å) [8]. Therefore, the crystal Sr 3 Lu 2 (BO 3 ) 4 (SLuB) may provide preferable condition for the doping of Er 3+ and Yb 3+ ions.…”
Section: Introductionmentioning
confidence: 99%